Interaksi Faktor-Faktor Penyebab Kecelakaan di Jalan Tol dengan Kesenjangan Kecepatan sebagai Pemicu Kejadian Tabrak dari Belakang pada Malam Hari di Jalan Tol Cipali - Afif Amir Amrullah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Traffic accidents due to rear-end collisions are the highest contributor to the death rate in traffic accidents that occur on toll roads. It is suspected that vehicle, environmental, weather and driver factors as well as high speed gaps contribute to the occurrence of accidents. This study aims to determine the relationship between vehicle, environmental, weather and driver factors with the occurrence of speed gaps through observations of rear light brightness levels, vehicle visibility and speed. This study uses a descriptive observational method. The sample is a vehicle that passes through the Cipali Toll Road KM 188-108 towards Jakarta, on Sunday, January 29, 2024 at 19.30-21.00 WIB. The observer vehicle speed is 80-100 km/hour. The brightness level is measured using a luxmeter. The results of the study obtained dark weather, no rain, some toll roads did not have street lights, there were 316 minibus, bus and truck vehicles that passed or passed the researcher's route. A total of 240 vehicles (75%) of the minibus type had appropriate rear light brightness, visibility and speed. As many as 56 vehicles (23%) of the truck type had low rear light brightness, poor visibility, and speeds below regulations, resulting in a high speed gap which has a high potential to cause rear-end collisions.